Do Financial Regulation and Technology Matter in Fostering Green Growth? - Dyah Maya Nihayah; Dwi Rahmayani; Afif Dhia Pratama; Fredericho Mego Sundoro; Agus Hermanto (Universitas Negeri Semarang, 2024)
Effective regulation and technological innovation are key factors in driving the implementation of green growth initiatives. This research investigates how financial regulation and technological innovation influence green growth, proxied by carbon productivity, with data from 1996 to 2020 across ASEAN-5 Countries. A Panel Dynamic Ordinary Least Square (DOLS) model is conducted to analyze the long-run effect on each variable. The result showed that financial regulation, proxied by regulatory quality and economic freedom, positively and significantly influences green growth. Meanwhile, technological innovation has a positive but not significant influence on green growth. According to the findings, this study proposes adopting top-tier regulations and a step-by-step approach to realizing green growth. Meanwhile, the government can also open an investment as funding to improve innovation in green technology